Clinical application of in vivo proton (1H) MR spectroscopy in musculoskeletal tumors. Issue 4 (2005) - Wang Wang, Chien-Kuo Chien-Kuo; Hsieh Hsieh, Tsyh-Jyi Tsyh-Jyi; Jaw Jaw, Twei-Shiun Twei-Shiun; Lin Lin, Jau-Nan Jau-Nan; Liu Liu, Gin-Chung Gin-Chung; Li Li, Chun-Wei Chun-Wei
Abstract : A technique called in vivo magnetic resonance spectroscopy (MRS) can be performed along with magnetic resonance imaging (MRI) to obtain information about the chemical content of musculoskeletal lesions. This information can be used for several clinical applications, such as improving the accuracy of lesion diagnosis and monitoring the response to cancer therapies. Initial MRS studies of musculoskeletal tumors show promising results, and the technique has been incorporating into the MRI routine protocols. This article introduces 1 H MRS of the musculoskeletal tumors, reviews the literature, discusses current methods and technical issues, and describes applications for treatment monitoring and lesion diagnosis.